2006
DOI: 10.1177/1077546306061127
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dynamics of Microelectromechanical Systems

Abstract: We investigate the dynamic behavior of a micromachined switch including a thin metal membrane called the “bridge”. A nonlinear model is presented considering mechanical force, electrostatic force, and the squeeze-film damping force, and the dynamic equations of a double model for the micromachined system are derived. The numerical simulation of the double model equations indicates that due to nonlinearity in the electrostatic force and the squeeze-film damping force, the micromachined switch undergoes period-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…with nonlinear electrostatic force, they demonstrated that the safe basin governing the system dynamics is eroded by the penetration of fractal tongues while increasing the excitation amplitudes. Liqin et al [15] investigated the dynamic response of a clamped-clamped microbeam with squeezefilm damping using the Galerkin method. They obtained force-response diagrams with period doubling bifurcations and chaotic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…with nonlinear electrostatic force, they demonstrated that the safe basin governing the system dynamics is eroded by the penetration of fractal tongues while increasing the excitation amplitudes. Liqin et al [15] investigated the dynamic response of a clamped-clamped microbeam with squeezefilm damping using the Galerkin method. They obtained force-response diagrams with period doubling bifurcations and chaotic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Stability of a microbeam resonator was studied 15 using phase plane diagrams and Poincare´mapping. Effects of quadratic and cubic nonlinearities due to nonlinear electrostatic forces and nonlinear damping, respectively, were investigated 16 utilising a ROM of a clamped-clamped microswitch.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the electrostatic force term is represented in its exact form unlike a truncated expansion series used by other existing models. [9][10][11]16,17 It may be highlighted that in order to include squeezefilm damping characteristic in their nonlinear dynamic model, previous researchers [7][8][9][10][11][12] have assumed a coefficient corresponding to linear viscous damping. The emphasis of the present work is on capturing the actual dynamic behaviour of a microcantilever under nonlinear squeeze-film damping with the damping coefficient being a nonlinear function of the beam displacement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed scheme shifts the dynamic pull-in, modeled as a homoclinic bifurcation, to higher excitation amplitudes. Liqin et al (2005) investigated the dynamic response of a microswitch using Euler-Bernoulli beam theory taking into account a nonlinear electrostatic force, squeeze-film damping, and residual stress. Using the Galerkin method with a two-mode approximation and a Taylor series expansion of the electrostatic force, they generated force-response curves.…”
Section: Introductionmentioning
confidence: 99%